Cedar Waxwing (Bombycilla cedrorum): WEC464/UW520, 6/2024 - Akhter , Muhammad Azeem; Hostetler, Mark (EDIS, 2024)
This fact sheet describes a common wintering bird in Florida called the cedar waxwing (Bombycilla cedrorum). Information in this fact sheet is relevant to homeowners, backyard bird enthusiasts, and the general public. Written by Muhammad Azeem Akhter and Mark Hostetler, and published by the UF/IFAS Department of Wildlife Ecology and Conservation, June 2024.